IMPROVING THE EFFICIENCY OF THE TECHNOLOGYCLEANING SEED COTTON FROM SMALL IMPURITIES AND ADDING NEW TECHNOLOGY (Journal of Science-Innovative Research in Uzbekistan, 2023)
In this article, our national wealth is faced with various problems in the processing of seed cotton from large and small impurities. In order to find a solution to these problems, it was determined as a result of the analysis that the machine for cleaning seed cotton from small impurities is more efficient than other models